2021
DOI: 10.3389/fnins.2020.593360
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and Dose of Neuromuscular Electrical Stimulation Influence Sensorimotor Cortical Excitability

Abstract: Neuromuscular electrical stimulation (NMES) of the nervous system has been extensively used in neurorehabilitation due to its capacity to engage the muscle fibers, improving muscle tone, and the neural pathways, sending afferent volleys toward the brain. Although different neuroimaging tools suggested the capability of NMES to regulate the excitability of sensorimotor cortex and corticospinal circuits, how the intensity and dose of NMES can neuromodulate the brain oscillatory activity measured with electroence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 75 publications
(50 reference statements)
1
30
0
Order By: Relevance
“…Although this study is the first to investigate the effects of transcutaneous spinal cord stimulation on cortical oscillations, other studies have reported neuromodulation through electrical stimulation of peripheral musculature and nerves [21,41,42]. For instance, Insausti-Delgado et al reported enhanced alpha and beta ERD during high intensity neuromuscular electrical stimulation of the wrist extensors [21]. They attributed this effect to the activation of muscle spindles and joint afferents which recruited proprioceptive fibres in the spinal cord, which in turn affected the motor cortex.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although this study is the first to investigate the effects of transcutaneous spinal cord stimulation on cortical oscillations, other studies have reported neuromodulation through electrical stimulation of peripheral musculature and nerves [21,41,42]. For instance, Insausti-Delgado et al reported enhanced alpha and beta ERD during high intensity neuromuscular electrical stimulation of the wrist extensors [21]. They attributed this effect to the activation of muscle spindles and joint afferents which recruited proprioceptive fibres in the spinal cord, which in turn affected the motor cortex.…”
Section: Discussionmentioning
confidence: 98%
“…As far as we are aware, no studies have yet considered tSCS-based neuromodulation in terms of sensorimotor cortical oscillations as measured from the electroencephalogram (EEG). Given reports of enhanced excitability of motoneuron and cortico-motoneuronal synapses through spinal stimulation, we would expect an expression of neuromodulation in terms of cortical oscillations, as is the case with other stimulation-based modalities such as functional electrical stimulation (FES) [21], and transcutaneous electrical nerves stimulation (TENS) [22]. The variety of modulation is a matter of conjecture, however.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that this study did not include a sham condition. Insausti-Delgado et al (2021) showed that neuromuscular electrical stimulation (NMES) over the wrist extensors resulted in an event-related Correlations were calculated for the sum score of the VIS and the KIS, and the change from baseline scores of EEG power in the theta, alpha, and beta range, both for the concurrent and delayed PEMS condition. A correlation between the VIS sum score and the change from baseline score of beta power was identified for the concurrent PEMS condition.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the Ia-afferent excitation to the α-motoneuron pool can attenuate destabilising joint movements while the enhancement of the activation of the α-motoneuron pool can facilitate instantaneous segmental reactions to the demands of the motor or postural task ( Paillard, 2017a ). At the cortical level, SES is likely to induce durable changes in motor cortex excitability that can be assimilated to enhance sensorimotor activity and connectivity ( Kaelin-Lang et al, 2002 ; Schröder et al, 2018 ; Insausti-Delgado et al, 2021 ). Enhanced sensorimotor activity could result from favourable impact of SES over postcentral and parietal cortices (primary somatosensory cortex and posterior parietal cortex) to precentral cortices (primary motor cortex) in the stimulated hemisphere ( Paillard, 2021 ).…”
Section: Motor and Postural Adaptations Induced By Electrical Stimulationmentioning
confidence: 99%